Experimental Approach to Active Mounts Using Electromagnetic Actuator and Rubber with Consideration of Shock Resistance for Naval Shipboard Equipment - Yun-ho Shin; Seok-jun Moon; Woo-jin Jung; Soo-ryong Bae (Shock and Vibration)
There is demand for stringent vibration isolation within machine installations in order to achieve maximum performance or to satisfy otherwise extreme criteria, particularly, when there is a strong source of vibration such as a motor pump. It is frequently necessary to prevent the transmission of these vibrations to other parts of the system for passenger comfort in vehicles, ships, trains, etc., or for the protection of delicate electronic equipment. In the defense sector, the need for equipment which is better at avoiding detection has led researchers to focus more on improving vibration isolation. In this paper, an active mount combined with a passive rubber mount and an electromagnetic actuator is proposed and examined for use in naval shipboard equipment. The electromagnetic actuator is suggested for improving performance and overcoming its inherent limitations which are caused by the friction between the magnet and coil. The design specifications of an active mount, such as required force, displacement, and frequency characteristics, are identified for the self-excited pump system, and then an electromagnetic actuator active mount is redesigned with considering the shape of the passive rubber mount and shock resistance. The performance was examined on the single active mount using an external exciter, which could be simplified as two-degree-of-freedom system, and also confirmed experimentally on an active mount system with four mounts using a motor system. From the results of applying the proposed electromagnetic active mount, a vibration reduction of about 20 dB for the motor equipment was observed for the excited frequency components of 1,600 rpm and its two harmonic components.